Correction: Integrated microRNA and mRNA signatures associated with overall survival in epithelial ovarian cancer. - Joanna Lopacinska-Jørgensen; Douglas V N P Oliveira; Guy Wayne Novotny; Claus K Høgdall; Estrid V Høgdall (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0255142.].